2020
DOI: 10.1016/j.aquatox.2019.105384
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tritiated water on locomotion of zebrafish larvae: a new insight in tritium toxic effects on a vertebrate model species

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…However, AChE activity was modified in adult fathead minnows exposed to HTO after depuration (Gagnaire et al 2020b). Moerover, genes involved in muscle contraction were modified by HTO (Arcanjo et al 2018), and swimming behavior of larvae was altered but only for one dose rate (Arcanjo et al 2020).…”
Section: Comparison Of Results For Hto/tritiated Thymidine/gamma Radiation Exposurementioning
confidence: 98%
See 1 more Smart Citation
“…However, AChE activity was modified in adult fathead minnows exposed to HTO after depuration (Gagnaire et al 2020b). Moerover, genes involved in muscle contraction were modified by HTO (Arcanjo et al 2018), and swimming behavior of larvae was altered but only for one dose rate (Arcanjo et al 2020).…”
Section: Comparison Of Results For Hto/tritiated Thymidine/gamma Radiation Exposurementioning
confidence: 98%
“…Tritiated water (HTO) effects were studied at dose rates of 3.4x10 1 , 1.36x10 2 and 1.26x10 3 µGy/h until larvae reached 10 dpf (days post fertilization), in order to observe a key phase of larval development until the total resorption of yolk bag, and therefore to investigate potential effects on metabolism (Gagnaire et al 2020a). The links between responses observed at the molecular, tissular and individual levels were also investigated using specific tools such as RNAseq (Arcanjo et al 2018) and behavioral analyses (Arcanjo et al 2020). Tritiated thymidine was also studied at dose rates of 8.7x10 1 to 2.4x10 3 µGy/h (Adam-Guillermin et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Arcanjo et al . [23, 24] exposed zebrafish eggs at two HTO concentrations corresponding to dose-rates of 0.4 mGy/h and 4 mGy/h, and investigated the effect on the transcriptome [ 23 , 24 ]. They reported that the genes involved in DNA repair such as h2afx , bcl2l and xrcc1 were upregulated when eggs were irradiated at 4 mGy/h, whereas the genes involved in promoting apoptosis were upregulated when eggs were irradiated at 0.4 mGy/h.…”
Section: Discussionmentioning
confidence: 99%
“…The fate of tritium, an isotope of hydrogen (half-life 12.3 y), in the human body, as tritiated water (HTO) or organically bound tritium (OBT), is well understood, with inhaled HTO translocated quickly into blood and distributed uniformly (Di Pace et al, 2008;Nie et al, 2021). Furthermore, tritium-induced biological effects have been extensively explored in aquatic biota under a range of radiation dose rates (Jha et al, 2005(Jha et al, , 2006Adam-Guillermin et al, 2012;Jaeschke and Bradshaw, 2013;Dallas et al, 2016a,b;Gagnaire et al, 2017;Festarini et al, 2019;Arcanjo et al, 2020). However, there is a gap in understanding related to the environmental fate and subsequent radiotoxicity of tritiated products.…”
Section: Introductionmentioning
confidence: 99%